2008
DOI: 10.2174/1874421400802010064
|View full text |Cite
|
Sign up to set email alerts
|

NcGRA2-RT-PCR to Detect Live Versus Dead Parasites in Neospora caninum-Infected Mice

Abstract: Abstract:In the present work, we optimized a recently established NcGRA2-RT-PCR based on RNA to detect live Neospora caninum parasites in tissue, and compared the results with the conventional inoculation of diagnostic specimen onto cell culture. C57BL/6 mice were experimentally infected with Nc-1 tachyzoites and subsequently euthanized 6 or 12 days post infection (dpi). Selected organs were used to search for parasites by (i) PCR using genomic DNA (gDNA), (ii) PCR using cDNA and (iii) in vitro inoculation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…In order to further study the effects of intra-nasal vaccination on parasite viability, we employed a recently developed NcGRA2-specific RT real-time PCR (Strohbusch et al 2008 a , b ), which allows quantification of the number of viable tachyzoites in brain tissue samples of the different experimental groups. The rational behind this assay is that NcGRA2-mRNA will only be detected when viable parasites are present, since mRNA is rapidly degraded upon cell death.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to further study the effects of intra-nasal vaccination on parasite viability, we employed a recently developed NcGRA2-specific RT real-time PCR (Strohbusch et al 2008 a , b ), which allows quantification of the number of viable tachyzoites in brain tissue samples of the different experimental groups. The rational behind this assay is that NcGRA2-mRNA will only be detected when viable parasites are present, since mRNA is rapidly degraded upon cell death.…”
Section: Resultsmentioning
confidence: 99%
“…To quantify the viable tachyzoites in brain samples, NcGRA2-RT-PCR was performed using the corresponding other hemisphere from each mouse (Strohbusch et al 2008 a , b ). Then 200 μl of chloroform was added to all brain samples stored in QIAzol™, and the upper phase, obtained after vigorously vortexing and centrifuging the sample for 2 min at 10 000 g , was transferred to a new tube.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar assays, albeit by detecting other RNA targets, have been developed earlier. For instance, one assay based on measuring of mRNA expression levels of dense granule antigen 2, a protein that is expressed in both tachyzoites and bradyzoites of N. caninum , has been used to quantify the viability of this parasite within infected host cells, and within infected tissue of experimentally infected animals ( Strohbusch et al, 2008a,b; Debache et al, 2009; Lizundia et al, 2009 ). More recently, van den Bogaart et al reported on the development and application of a duplex quantitative reverse transcriptase PCR for simultaneous assessment of drug activity against Leishmania intracellular amastigotes and their host cells, by quantifying Leishmania 18S ribosomal RNA and the human beta-2-microglobulin mRNA ( van den Bogaart et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…31 While supporting tumor regression, the activation of the immune system also allows Neospora elimination. Although the latter is well described in the literature, 32 we aimed to assess if the presence of lung tumor could affect Neospora distribution after intranasal administration. No difference in distribution was found between tumor bearing and healthy mice (online supplemental table 3).…”
Section: N Caninum Is Associated With Therapeutic Effect Against Meta...mentioning
confidence: 99%